2008
DOI: 10.1093/ageing/afp002
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscess in the elderly: clinical features, outcomes and prognostic factors

Abstract: Background: pyogenic liver abscess (PLA) is a potentially life-threatening disease in middle-to-old aged persons. Objective: to compare the differences in clinical features and outcomes between older and younger PLA patients, and to identify predictors of outcomes in older patients. Design: retrospective chart review of all PLA patients between July 1999 and June 2007. Setting: a 1,600-bed primary and tertiary care centre. Subjects: in total, 339 patients were enrolled and included 118 ≥65 years of age (the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 24 publications
6
46
1
1
Order By: Relevance
“…Whilst decades ago pyogenic liver abscesses were mostly seen as a complication of acute abdominal infections such as acute appendicitis, today the mean age of patients has increased and bacterial liver infections are found to be associated with malignant diseases and modern tumour therapy [22][23][24]. Thus, the potential use of moxifloxacin for antibiotic prophylaxis is brought into focus.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst decades ago pyogenic liver abscesses were mostly seen as a complication of acute abdominal infections such as acute appendicitis, today the mean age of patients has increased and bacterial liver infections are found to be associated with malignant diseases and modern tumour therapy [22][23][24]. Thus, the potential use of moxifloxacin for antibiotic prophylaxis is brought into focus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they proposed that case fatality in older PLA patients was possibly related to host conditions, rather than to the characteristics of PLA itself. 11 In another large series of culture-confirmed PLA investigation, it was shown that malignancy and septic shock increased the mortality of PLA. 12 A previous nationwide study suggested that renal disease and malignancy correlated with higher death rates in all PLA patients.…”
mentioning
confidence: 99%
“…In addition to K. pneumoniae, other causative agents such as E. coli and polymicrobial with or without anaerobic bacteria were also more frequently found in older patients. 11,12 Previous studies revealed that a high ratio of hepatobiliary malignancy was found in non-K. pneumoniae patients. 8 Physicians should pay attention to the associated malignancy in geriatric PLA patients, which can lead to a poor prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…L'hyperphosphatasémie alcaline est l'élément le plus fréquent (90 % des cas). Les facteurs pronostiques péjoratifs sont : l'âge extrême du patient, avec une mortalité pouvant atteindre 80 % chez l'enfant et après 75 ans [3,4] ; les causes biliaires fréquemment compliquées d'abcès multiples ;…”
unclassified